A comprehensive molecular insight into host-guest interaction of Phenanthrene with native and ionic liquid modified beta-cyclodextrins: Preparation and characterization in aqueous medium and solid state - Hui, Boon Yih (Elsevier, 2020)
The inclusion complexes of Phenanthrene with native beta CD and ionic liquid modified beta CD were prepared and investigated in both solid and solution states. The formation of the inclusion complexes were successfully monitored by FTIR, TGA, DSC, 1D H-1 NMR, 2D NOESY NMR and UV-vis spectroscopy. The results revealed that Phenanthrene formed 1:1 stoichiometry ratio for both host-guest inclusion complexes with an apparent formation constant of 239.7 M-1 for native beta-cyclodextrin, which was higher than ionic liquid modified beta-cyclodextrin (14.9 M-1). The NMR studies showed that Phenanthrene penetrated into the cavity of both cyclodextrins (CDs) from the more accessible wider side. For beta CD, Phenanthrene displayed one mode of binding, i.e., formation of an inclusion complex. Meanwhile, ionic liquid modified beta-cyclodextrin demonstrated two modes of binding, i.e. inclusion in the CD cavities and interaction with the outer surface of the CD molecules, mainly near the ionic liquid (IL) group. (C) 2020 Elsevier B.V. All rights reserved.